2008
DOI: 10.1093/pcp/pcn141
|View full text |Cite
|
Sign up to set email alerts
|

GFP Tagging of Sieve Element Occlusion (SEO) Proteins Results in Green Fluorescent Forisomes

Abstract: Forisomes are Ca2+-driven, ATP-independent contractile protein bodies that reversibly occlude sieve elements in faboid legumes. They apparently consist of at least three proteins; potential candidates have been described previously as ‘FOR’ proteins. We isolated three genes from Medicago truncatula that correspond to the putative forisome proteins and expressed their green fluorescent protein (GFP) fusion products in Vicia faba and Glycine max using the composite plant methodology. In both species, expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
81
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 41 publications
0
81
0
Order By: Relevance
“…Most of these herbivores have distinct geographical distributions, resulting in divergent herbivore communities across latitudinal (Züst et al, 2012), longitudinal (Kozlov, 2008), and altitudinal gradients (Pélissier et al, 2008). The pronounced geographical heterogeneity of herbivore communities coincides with considerable variation in herbivore resistance and expression of defensive traits in many plants (Johnson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these herbivores have distinct geographical distributions, resulting in divergent herbivore communities across latitudinal (Züst et al, 2012), longitudinal (Kozlov, 2008), and altitudinal gradients (Pélissier et al, 2008). The pronounced geographical heterogeneity of herbivore communities coincides with considerable variation in herbivore resistance and expression of defensive traits in many plants (Johnson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, four sieve element occlusion (SEO) gene family members have been identified in Medicago truncatula (MtSEO-F1-F4) and Glycine max (GmSEO-F1-F4) and characterized as encoding forisome subunits, which assemble into a special type of crystalloid P-protein found uniquely in Fabaceae (23)(24)(25)(26)(27)(28). Forisomes differ from conventional P-proteins because they can undergo a reversible switch between condensed spindle-shaped and dispersed plug-forming states, triggered by a calcium influx (29,30).…”
mentioning
confidence: 99%
“…Light and confocal laser scanning microscopy studies have demonstrated that forisomes, crystalloid P-proteins found in Vicia faba and other faboid legumes, control the conductivity of sieve tubes (Knoblauch et al, 2001(Knoblauch et al, , 2003. The components of the forisomes have been identified and appear to be proteins unique to faboid legumes, although some of the motifs they contain have been identified in proteins from other plant taxa (Noll et al, 2007;Pelissier et al, 2008). These findings demonstrate a role of forisome-type P-proteins in the occlusion of sieve tubes in the Fabaceae, but the function of the P-proteins present in other species remains unclear.…”
mentioning
confidence: 99%